In-Situ Towed Sampling Device for Integrated Calibration and Monitoring of Surface Water Microplastics - Guerin, Caitlin (My University, 2018)
Current advancements in the emerging technology of embed sensors for ocean research now offers opportunities to apply low-cost solutions for real-time investigation of the spatial distribution of microplastics and particles. Microplastics absorb and transfer chemicals that cause organisms to be intoxicated or starved. This project is focused on the design and development of a prototype sensor for in-situ measurements of microplastic concentrations. This device makes use of data from optical interruptions of particles in a flow through water stream onboard a towed platform relayed to a ship board computer via USB. The prototype device consists of 5 components (1) architecture of the water sample flow-through system; (2) the selection of photo interrupter sensors for particle detection; (3) inclusion of a filter net and codend collection for calibration; (4) the layout of these components on a towed platform; and (5) the power and data communication requirements. Results show the spatial variability of microplastic and particle concentrations. An overall rough positive correlation between particle and microplastic concentrations is observed at Shilshole Bay Marina. Tests confirm the stability and ability of the device to take particle and microplastic measurements.
Keywords: microplastics; Shilshole Bay